JENIS-JENIS BURUNG (AVES) DI PERSAWAHAN DESA PASIR BARU KABUPATEN ROKAN HULU RIAU - -, Jurati; Ade, Filza Yulina; -, Dahlia (Jurnal Ilmiah Mahasiswa FKIP Prodi Biologi, 2015)
Bird isa vertebrate which hasfeataer, reproduce by of laying eggs and help pollination, pest predator and supporting ecosystems. The alm of this study was to determine the species of birds in the rice field area of Sand VillagePasir Baru Rokan Hulu. This study was conducted in December 2014 to January 2015 with survey methods. Samples colleceted with random sampling. Results showed4 orders, 8 families, 9 genera and 12 species, with total 167 individuals. The species were Bubulcus ibis, Halcyon smyrnensis, Hirundo rustica, Lonchura leucogastroides, L. maja, L. punculata, L. striata, Padda oryzivora, Passer montanus, Prinia familiaris, Pycnonotus goiavier and Streptopelia chinensis.